2011
DOI: 10.1111/j.1532-849x.2011.00759.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Horizontal Misfit and Bar Framework Material on the Stress Distribution of an Overdenture-Retaining Bar System: A 3D Finite Element Analysis

Abstract: The levels of static stresses seem to be closely linked with horizontal misfit, such that its amplification caused increased levels of stress in the structures of the overdenture-retaining bar system. On the other hand, the stiffness of the bar framework presented a lower effect on the static stress levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
33
1
7

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(45 citation statements)
references
References 19 publications
4
33
1
7
Order By: Relevance
“…Use of FE analysis helps to overcome some traditional experimental methodological limitations, by offering information about the biomechanics of a given situation. [13][14][15][16] However, FE analysis presents some limitations due to simplifications made in the analysis. The assumption of homogeneous, isotropic, and linearly elastic properties for the bone is common in the literature, [13][14][15][16] but could affect the reliability of the results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Use of FE analysis helps to overcome some traditional experimental methodological limitations, by offering information about the biomechanics of a given situation. [13][14][15][16] However, FE analysis presents some limitations due to simplifications made in the analysis. The assumption of homogeneous, isotropic, and linearly elastic properties for the bone is common in the literature, [13][14][15][16] but could affect the reliability of the results.…”
Section: Discussionmentioning
confidence: 99%
“…The elastic properties used (Table 1) were taken from the literature. [13][14][15][16] Convergence tests, with 6% confidence levels, were performed to guarantee that the results were not influenced by the FE mesh. The implant thread was removed to reduce the number of elements.…”
Section: Methodsmentioning
confidence: 99%
“…Different prosthetic designs as well as multiple types of materials have been used to fabricate prosthetic frameworks . A truly passive fit of screw‐retained prostheses onto both vertical and tilted implants has been reported to be mandatory to avoid tensile, compressive, and bending forces, which may be dangerous for the osseointegration process and/or result in failure of the components . However, some studies have found that dental implants tolerate certain levels of misfit …”
mentioning
confidence: 99%
“…The absence of a passive fit in the implant-prostheses interface increases stress concentration on the supporting tissues, due to the intimate bone-implant contact (1)(2)(3)(4). A misfit in the denture frameworks can cause many complications, including biological effects such as inflammation of the surrounding tissue, pain, bone deformation and remodeling, continual resorption or even the loss of osseointegration (5).…”
Section: Introductionmentioning
confidence: 99%